Intersectionalities of the Left and Right in Latin America and Europe. An exploration of contemporary political processes - Nicol A. Barria-Asenjo; Slavoj Žižek; Brian Willems; Ruben Balotol; Gonzalo Salas; Jesús Ayala-Colqui (Íconos)
The current rise of new right-wing groups with a particular combination of intransigent economic liberalism and conservative nationalist fascism, a kind of liberfascism, advocates for both a strict apology for the capitalist market and the exclusion of anything that challenges its model in the political and cultural spheres. Based on the populist discourse that exploits the discontent caused by neoliberal democracy, they gain followers for nationalist, cultural, and racist reasons that in the end are nothing more than right-wing deception to protect the rule of capital. Faced with the restoration of an already exhausted neoliberal model, an intersectionality appears between the Left and the Right which, far from confirming the diagnosis of the end of ideologies and the deactivation of the class struggle, rekindles conflicts over capital. This article deals with such a situation. It argues how intersectionality is not a privilege of the Left, but is also used by the extreme populist Right to channel discontent and propagate its particular brand of oppression. It is concluded, based on examples of struggles in Latin America and Europe, that an intersectional and transversal politics must be developed in the face of the hegemony of the new populist and nationalist Right; the political tactic must not be local, but must pursue a new international strategy.